Curcumin-Mediated Inhibition of L-Tryptophanase activity: Purification and Characterization from Escherichia coli (Journal of the College of Basic Education, 2026)
The study's objective was to use curcumin to limit the activity of the enzyme L-tryptophanase (Tnase).Curcumin is known as diferuloylmethane (C21H20O6) has minimal or no cytotoxicity and antioxidant qualities, curcumin is naturally occurring bioactive compound made from Curcuma longa L. rhizomes. According to the inhibition results higher curcumin levels of 250 µg/ml demonstrated 100% L-tryptophanase inhibitory activity, whereas lower curcumin concentration of 62.5 µg/ml demonstrated 95% inhibitory efficacy. The L-tryptophanase is considered a virulence-associated factor that play a role in the development and progression of infection. The enzyme was purified from E. coli isolated from a urinary tract infection via precipitation with 70% ammonium sulphate saturation and ion exchange chromatography, in addition to gel filtration chromatography using a Sephadex G-150 column. During the final purification stage, the crude enzyme's specific activity increased from 13.5 U/mg protein to 71.4 U/mg protein. According to the study's pure enzyme characterization, the impacts of pH and pH stability, along with temperature and temperature stability, were the results appeared 8, 8 and 37, 32, and 42 °C, respectively.